The Relationship between Husband’s Support and the Readiness of Pregnant Women in Facing Labor - Devi Nurlelis; Ririn Indriani; Lumastari Ajeng Wijayanti; Dwi Estuning Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2026)
ABSTRACT Due to the labour, pregnant women often experience emotional changes such as anxiety, fear, and stress. Data showed that out of 56 pregnant women, 73.2% experienced moderate anxiety and 14.2% severe anxiety, with 62.5% of the severe anxiety group having poor labour readiness. This shows a tendency that high anxiety has an impact on low readiness for labour. One of the factors that influences labour readiness is support from the husband, as the closest person to the wife. This study aimed to find out the relationship between husbands' support and the readiness of pregnant women to face labour. This study used a correlational design with a cross-sectional approach. The population consisted of 43 people, with a sample of 39 respondents selected using simple random sampling. The instruments used were the husband’s support questionnaire and the readiness to face labour questionnaire. The questionnaires were tested for validity and reliability prior to data collection using the Pearson Product Moment for validity and Cronbach’s Alpha for reliability. The validity test showed r-values > r-table value (0.576), while the reliability test yielded Cronbach’s Alpha values of 0.903 and 0.906. Data analysis used the Spearman Rank Test. The results showed a value of r = 0.334 with p value = 0.037 (p < 0.05), which means there is a significant relationship between husband support and the readiness of pregnant women in facing childbirth. The results showed that active husband involvement during pregnancy and childbirth plays an important role in supporting maternal psychological readiness.